The Influence of the Management Problem-Based Learning Model with Pop-Up on the Cognitive Abilities - Saputri, Firliya Dwi; Nafiah, Jamilatun (Journal of Educational Management Research, 2025)
The purpose of this study is to investigate the impact of the PBL model with Pop-Up media on cognitive abilities in madrasah. The background of this study is based on the low understanding of students towards the concept of citizenship and the dominance of the lecture method in learning. The study employed a quantitative approach with an experimental design, specifically a one-group pretest-posttest Design. The sample used 25 students. The research instrument was a 16-item questionnaire that had undergone validity and reliability tests. The results of the normality test showed that the data were normally distributed, and the Paired Sample T-Test showed a significant score of 0.000 < 0.05. This demonstrates a substantial impact of applying the PBL model with Pop-Up media on enhancing students' cognitive abilities. This study concludes that the combination of the PBL model and Pop-Up media is efficacious in improving student learning outcomes in the Pancasila Education subject. This study emphasizes the importance of innovative teaching methods, such as the PBL model with Pop-Up media, in enhancing students' cognitive abilities. For educational management, incorporating such methods can improve student engagement, promote critical thinking, and align teaching practices with contemporary pedagogical needs.